The effect of a sonographic estimated fetal weight on the risk of cesarean delivery in macrosomic and small for gestational-age infants*. (19th May 2017) - Matthews, Kathy C.; Williamson, John; Gupta, Simi; Lam-Rachlin, Jennifer; Saltzman, Daniel H.; Rebarber, Andrei; Fox, Nathan S.
Abstract: Objective : To assess the association of a sonographic estimated fetal weight (sonoEFW) with the risk of cesarean delivery in women with macrosomic or small for gestational age (SGA) infants. Methods : Retrospective cohort of singleton deliveries >24 weeks by one MFM practice from 2005 to 2014. We included all patients who delivered an infant with macrosomia (birth weight ≥4000 g) or SGA (birth weight <10th percentile). We compared the risk of cesarean delivery between patients who did and did not have a sonoEFW within four weeks of delivery. Regression analysis was performed to control for any differences in baseline characteristics. Results : In patients with macrosomic infants ( n  = 352), the risk of cesarean delivery was significantly higher in the sonoEFW group (45.3% versus 17.6%, aOR 2.144, 95% CI: 1.06–4.34). When we restricted the analysis to the subgroup of 265 patients who attempted vaginal delivery, our results were similar (22.3% versus 9.1%, aOR 2.73, 95% CI: 1.15–6.48). In patients with an SGA infant ( n  = 614), the risk of cesarean delivery was not higher in the sonoEFW group (37.4% versus 24.1%, aOR 1.23, 95% CI: 0.80–2.07), nor in those who attempted vaginal delivery (19.8% versus 13.7%, aOR 1.17, 95% CI: 0.62–2.21). Conclusions : A sonoEFW prior to delivery is independently associated with cesarean delivery in women with macrosomic infants, but not those with SGA infants. This should be considered when deciding to obtain a sonoEFW at the end of pregnancy, particularly if not for an accepted indication.